Student’s Perceptions in Writing Class by using Google Classroom in Pandemic Covid-19 - Irawati, Tatik (Program Studi Pendidikan Agama Islam Fakultas Agama Islam Universitas Nurul Huda, 2020)
This study aims to know the student’s perceptions in writing class by using Google Classroom in pandemic covid-19. Perception refers to how the brain sensory information. A person’s positive perception arises because of an individual’s satisfaction towards the object perceived and the existence of an individual’s experiences toward the object perceived. The methodis a descriptive case study that investigates a single case to produce an in-depth description of implementing Google Classroom online learning in writing class at STKIP PGRI Jombang. The qualitative data by using interviews of some students using an online questionnaire through Google form. The variable of this research is teaching paragraph writing using online learning through Google Classroom, while another variable of this research is students’ perceptions and consists of 30 students. The conclusion is students have positive perceptions of Google Classroom in writing class. With this finding, students maintain that Google Classroom makes their learning easier and useful for their online learning in writing class. The students thought by using Google Classroom in online learning is a good idea, and they plan to use it in the future. They also realize the importance of using technology to support their learning process. Therefore, students suggest using Google Classroom in the teaching and learning process during this pandemic era.